Psychosocial risk in newly diagnosed HIV-positive patients (Colombia Medica, 1994)
Serologic confirmation of human immunodeficiency virus (HIV) positivity generates unpredictable emotional responses. To evaluate the psychiatric status of patients at the time of this diagnosis and its impact on family functioning, a case-control study was conducted in Cali, Colombia. Single marital status, homosexual or bisexual behavior, and family dysfunction (family APGAR< 14 points) were associated with HIV seropositivity (X2= 35.6,p < 0.00001). The existence of some degree of psychopathology (Lubarsky Global Psychiatric Rating Scale